2002
DOI: 10.1159/000064134
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Residual Hearing in Children and Post-Lingually Deafened Adults after Cochlear Implantation: An Initial Study

Abstract: Objective: To investigate whether the residual hearing of severely hearing-impaired children and adults could be preserved using the soft surgery approach. Patients and Methods: This project employed a prospective study design. All testing and surgery took place in the Institute of Physiology and Pathology of Hearing, Warsaw, Poland. Twenty-six patients (7 children and 19 post-lingually deafened adults) with residual hearing were assessed. Subjects were assessed using conventional pure-tone audiometry at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 7 publications
5
74
2
7
Order By: Relevance
“…It has been reported that 64% of 219 patients with cochlear implants have a reduction of less than 10 dB in residual hearing after cochlear implantation (Clark, 1995). Similar reductions of 9 dB HL (Skarzynski et al, 2002) and 12 dB HL (Hodges et al, 1997) have been reported by other groups. While these changes in hearing thresholds after cochlear implantation are not necessarily related to post-implant fibrosis within scala tympani, these data can be used to place an upper boundary on the increase in damping that occurs after implantation within the measured frequency range.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been reported that 64% of 219 patients with cochlear implants have a reduction of less than 10 dB in residual hearing after cochlear implantation (Clark, 1995). Similar reductions of 9 dB HL (Skarzynski et al, 2002) and 12 dB HL (Hodges et al, 1997) have been reported by other groups. While these changes in hearing thresholds after cochlear implantation are not necessarily related to post-implant fibrosis within scala tympani, these data can be used to place an upper boundary on the increase in damping that occurs after implantation within the measured frequency range.…”
Section: Discussionsupporting
confidence: 87%
“…Efforts towards this goal essentially consist of atraumatic electrode insertion. This may include implanting directly through the round window or through an extension of the round window rather than making a large surgical cochleostomy, and the use of shorter, more delicate electrode arrays (Gantz and Turner, 2003;Skarzynski et al, 2002). Nonetheless, one very distinct histological change after cochlear implantation is the formation of scar tissue around the electrode (Alexiades et al, 2001;Araki et al, 2000;Miyamoto et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, animal experiments have shown that implantation of electrode carriers in the cochlea with preservation of functional structures, at least apical to the position of the electrode carrier, is possible [Xu et al, 1997]. Subsequent clinical studies reported that hearing preservation could also be achieved in human cochlear implantation [Skarzynski et al, 2002]. Using a modified surgical technique, we were able to preserve hearing within 20 dB of the mean preoperative values in 12 out of 14 subjects and within 10 dB in 9/14 subjects [Kiefer et al, 2004a].…”
Section: Introductionmentioning
confidence: 79%
“…Brimacombe et al [1994], Rizer [1988] and Kiefer et al [1999] reported a post-implantation loss of residual hearing in the vast majority of implanted patients. A partial preservation of residual hearing after cochlear implantation was reported by Hodges et al [1997], Dye et al [1987], Skarzynski et al [2002], and in a recent multicenter European study [James et al, 2005]. In contrast, Webb et al [1988] and Clark et al [1988] accomplished the insertion of electrodes with minimal histopathological trauma to intracochlear structures, including neural elements.…”
Section: Introductionmentioning
confidence: 94%